Personal Belief Exemptions for School-Entry Vaccinations, Vaccination Rates, and Academic Achievement - Nicole L. Hair; Anja Gruber; Carly Urban (Institute of Labor Economics (IZA), 2020)
Nonmedical exemptions from school-entry vaccine mandates are receiving increased policy and public health scrutiny. This paper examines how expanding the availability of exemptions influences vaccination rates in early childhood and academic achievement in middle school. We leverage 2003 legislation that granted personal belief exemptions (PBE) in Texas and Arkansas, two states the previously allowed exemptions only for medical or religious regions. We find that PBE decreased vaccination coverage among black and low-income preschoolers by 16.1% and 8.3%, respectively. Furthermore, we find that those cohorts affected by the policy change in early childhood performed less well on standardized tests of academic achievement in middle school. Estimated effects on mathematics and English Language Arts test scores were largest for black students, especially those residing in economically disadvantaged counties.
Keywords: H75; I12; I18; I21; I24; I28; 330; vaccination; state mandates; nonmedical exemptions; test scores